Analisis Faktor-Faktor yang Mempengaruhi Pengungkapan Tanggung Jawab Sosial Perusahaan (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021) - Indriyani, Devi Fajar; Sudaryanti, Dwiyani; Hariri, Hariri (Universitas Islam Malang, 2023)
This study aims to analyze the factors that influence the Disclosure of Corporate Social Responsibility. This research is a quantitative research with secondary data sources using annual reports and sustainability reports obtained through the official website of the Indonesia Stock Exchange (BEI) and the official website of each company.The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period, sampling using a purposive sampling technique obtained a sample of 66 companies, with the 2019-2021 period so as to obtain a total sample of 198. The data obtained will be calculated, tested and reprocessed on the hypothesis proposed using Software Statistical Product and Service Solutions (SPSS) 25 for windows.The results of the study show that Profitability, Company Size, and Leverage have a significant simultaneous effect on the Disclosure of Social Responsibility of manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Profitability has no effect on the Disclosure of Social Responsibility of manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Company Size has a positive and significant effect on the Disclosure of Social Responsibility of manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Leverage has no effect on the Disclosure of Social Responsibility of manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period.Keywords : Profitability, company size, leverage, disclosure of corporate social responsibility